2009
DOI: 10.1088/0953-4075/42/24/245001
|View full text |Cite
|
Sign up to set email alerts
|

A spherical-box approach for resonances in the presence of the Coulomb interaction

Abstract: The spherical-box approach is extended to calculate the resonance parameters and the real part of the wavefunction for single particle resonances in a potential containing the long-range Coulomb interaction. A model potential is taken to demonstrate the ability and accuracy of this approach. The calculated resonance parameters are compared with available results from other methods. It is shown that in the presence of the Coulomb interaction, the spherical-box approach works well for not so broad resonances. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 37 publications
(61 reference statements)
2
25
0
Order By: Relevance
“…The Mg and Ne isotopes have been studied in details. It was found that in 42,44 Mg, there appears a decoupling of the halo orbitals from the deformation of the core: The core is prolate, but the halo has a slightly oblate shape. The generic conditions for the occurrence of this decoupling effects have been given: the existence and the deformation of a possible neutron halo depends essentially on the quantum numbers of the main components of the single particle orbitals in the vicinity of the Fermi surface.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…The Mg and Ne isotopes have been studied in details. It was found that in 42,44 Mg, there appears a decoupling of the halo orbitals from the deformation of the core: The core is prolate, but the halo has a slightly oblate shape. The generic conditions for the occurrence of this decoupling effects have been given: the existence and the deformation of a possible neutron halo depends essentially on the quantum numbers of the main components of the single particle orbitals in the vicinity of the Fermi surface.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…In exotic nuclei, the neutron (or proton) Fermi surface is close to the particle continuum; thus, the contribution of the continuum is important [190][191][192][193][194][203][204][205][206][207][208][209][210][211][212][213][214][215][216][217][218]. Many methods or models developed for the studies of resonances [219] have been adopted to locate the position and to calculate the width of a nuclear resonant state, e.g., the analytical continuation in coupling constant (ACCC) method [220][221][222][223][224][225], the real stabilization method [226][227][228][229][230][231], the complex scaling method (CSM) [232][233][234][235], the coupled channels method [236][237][238], and some others [239,240].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the study of nuclear single-particle resonant states, especially those in exotic nuclei with unusual N/Z ratios becomes more and more important [46,47,48,49,50,51,52,53,54]. There have been some numerical studies on the PSS [55,56,57,58] and SS [59] in single particle resonant states.…”
Section: Introductionmentioning
confidence: 99%